Evaluasi Aplikasi Anterin Menggunakan Metode Pengujian Usability - Rosa Guriarsa Priambodo; Satrio Hadi Wijoyo; Retno Indah (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Anterin is a New transportation provider application that offers several services. These services are transportation services, courier services. The Anterin application has grown rapidly by seeing the Anteriny application being downloaded more than tens of thousands of times. However, users agree with the Anterin application that it still has disadvantages, which are requested by the compilation map to determine the location that is still lacking and the destination location that the user entered is not required by the application. From the feedback provided by users, the Anterin application still has a number of questions going on. Therefore, Anterin applications require excavation of problems and measurement of usability. The method used in this study is the method used to test used for discussion on the Anterin application and to measure the usefulness of the Anterin application using the assignment scheme and questionnaire. Tests were carried out on 5 respondents from users of the new Anterin application and questionnaires were filled out by 100 active user respondents from the Anterin application. The results of the evaluation indicate the problem and level of use of the Anterin application. The problem with the Anterin application is that participants who have difficulty making payments, participants who find it difficult to find a home address or location that challenges participants in the